2022
DOI: 10.11606/s1518-8787.2022056003964
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose, vulnerabilidades e HIV em pessoas em situação de rua: revisão sistemática

Abstract: OBJETIVO Analisar, sistematizar e compilar os fatores de vulnerabilidade (social, individual e programática) associados à tuberculose e HIV em pessoas em situação de rua. MÉTODOS Revisão sistemática de literatura de publicações quantitativas sobre tuberculose em pessoas em situação de rua entre os anos de 2014 e 2020, seguindo o guia de recomendações PRISMA e, para análise de viés, a ferramenta Joanna Briggs Institute Critical Appraisal. Agrupou-se as publicações segundo as vulnerabilidades. RESULTADOS Entre 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
0
3
0
9
Order By: Relevance
“… 10 Additional reviews provided prevalence data (per 100 000) from Japan (n=1400), Brazil (n=2800), Ethiopia (n=2600), and the USA (n=6000). 31 , 47 Incidence rates were obtained from primary or database studies, ranging from 31 cases to 900 cases per 100 000, and were scarce outside of the USA. 2 , 12 , 31 , 47 Prevalence ratios ranged from 22·4 (Sweden) to 461·2 (USA) on the basis of a single review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Additional reviews provided prevalence data (per 100 000) from Japan (n=1400), Brazil (n=2800), Ethiopia (n=2600), and the USA (n=6000). 31 , 47 Incidence rates were obtained from primary or database studies, ranging from 31 cases to 900 cases per 100 000, and were scarce outside of the USA. 2 , 12 , 31 , 47 Prevalence ratios ranged from 22·4 (Sweden) to 461·2 (USA) on the basis of a single review.…”
Section: Resultsmentioning
confidence: 99%
“… 31 , 47 Incidence rates were obtained from primary or database studies, ranging from 31 cases to 900 cases per 100 000, and were scarce outside of the USA. 2 , 12 , 31 , 47 Prevalence ratios ranged from 22·4 (Sweden) to 461·2 (USA) on the basis of a single review. 10 …”
Section: Resultsmentioning
confidence: 99%
“…Overall, Tuberculosis is known to be the most prevalent opportunistic infection in HIV-positive people [ 11 ]. It is the primary cause of mortality in these patients [ 16 ], and responsible for one-third of all HIV-related deaths [ 17 ]. In some studies, it has been found that up to 40% of HIV patients who passed away had also TB [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A detecção precoce da soropositividade faz parte da prevenção no combate à tuberculose e, assim, possibilita o atendimento clínico e terapêutico adequado aos pacientes infectados pelo HIV (SANTOS et al, 2017;RABAHI et al, 2017;SILVA et al, 2018). Portanto, a terapia antirretroviral imediata é fundamental, pois o HIV é conhecido por promover o desenvolvimento de TB (CAMPOY et al, 2019;GIOSEFFI;BATISTA;BRIGNOL, 2022).…”
Section: Introductionunclassified